Screening for Cancer: Publications 1971—1980 - Wagner, G.; Tautu, P.; Wolber, U. (Methods of Information in Medicine, 1981)
The number of publications dealing with different aspects of the problems of screening for cancer is growing so fast that only very few specialists can have a complete knowledge of the literature in this domain. For this reason, we are restricting our compilation to relevant publications from 1971—1980. We deliberately omitted short notes, abstracts, editorials, technical reports, letters to the editor as well as papers written in a language with restricted circulation (e. g. Russian and Japanese). Nevertheless, the bibliography includes almost 1,200 titles.As D. M. Eddy noticed in 1980, the screening problem resembles many other problems in medicine: it is important, it is urgent, but it is also very complicated. We experienced this complexity when trying to fit the many aspects of our topic into a classification. This finally took the following shape: